Derinat® has an immunomodulatory and anti-inflammatory effect on the model of acute lung injury in male SD rats - Palikova, Yulia A.; Palikov, Victor A.; Novikova, Nadezhda I.; Slashcheva, Gulsara A.; Rasskazova, Ekaterina A.; Tukhovskaya, Elena A.; Danilkovich, Alexey V.; Dyachenko, Igor A.; Belogurov Jr., Alexey A.; Kudriaeva, Anna A.; Bugrimov, Daniil Y; Krasnorutskaya, Olga N.; et al. (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is one of the leading causes of morbidity, as well as 40% of mortality among terminally ill patients. To simulate ALI in SD rats we used a two-hit model involving the administration of lipopolysaccharide (LPS) followed by hyperventilation of the lungs (HVL). We confirmed that the use of LPS followed by HVL leads to functional changes in the respiratory system and an increase in the blood serum concentration of inflammatory cytokines. We also showed that LPS+HVL after 4 hours lead to pronounced histological signs of lung damage. All these features are characteristic of the clinical picture of ALI. We have studied the effectiveness of Derinat® when administered intramuscularly at dose of 7.5 mg/kg for 8 days in the ALI model. Derinat® administration led to an increase in the concentration of most of the studied cytokines in a day. In the ALI model the administration of Derinat® blocks hypercytokinemia and returns the concentration of cytokines to its original values already 48 hours after the damaging effect of LPS + HVL, and also normalizes the parameters of pulmonary respiration in comparison with animals without treatment. By the 8th day after LPS + HVL, respiratory parameters and cytokine levels, as well as biochemical and hematological parameters did not differ between groups, while residual effects of lung damage were found in all animals. Histological examination of the lungs showed that the administration of Derinat® led to more pronounced perivascular lymphocytic-macrophage infiltration of lung tissue caused by damaging agents LPS+HVL, which may indicate stimulation of the local immune response. Thus, the administration of Derinat® stimulates the immune response, which is expressed in an increase in the level of cytokines, and also has a pronounced protective effect against damage caused by ALI, characterized by an improvement in respiratory function in comparison with animals without treatment. The immunomodulatory effect of Derinat® is expressed in a decrease in the cytokines level in response to ALI. In addition, Derinat® probably stimulates a local immune response in lung tissues. Thus, Derinat® is a promising treatment for ALI.